Main consequences of IFRS adoption: analysis of existing literature and suggestions for further research - Lourenço, I.; Branco, M. (Revista Contabilidade e Finanças, 2015)
This study characterizes the results of scientific research on the effect of adopting the International Financial Reporting Standards (IFRS) that have been published in the most prestigious scientific journals in the field of accounting at the international level and it identifies avenues for further research. Based on the analysis of a set of 67 articles published by the accounting journals that make up the Social Sciences Citation Index (SSCI), published between 2000 and 2013, it is concluded that, as a general rule, IFRS adoption has a positive effect on information quality, the capital market, analysts' ability to predict, comparability, and information use. Nevertheless, this effect depends on some factors, such as country's characteristics (namely, the enforcement level) and companies' characteristics. Sharing rules is not, by itself, enough to create a common business language, and management incentives and institutional factors play a major role in framing the characteristics of financial reporting. Finally, some gaps are identified in the literature and avenues for further research are introduced.